Mitogen-activated protein kinase-mediated Fas apoptotic signaling pathway - Goillot, Evelyne (The National Academy of Sciences of the USA, 1997)
Ligation of the cell surface receptor Fas/APO-1 (CD95) by its specific ligand or by anti-Fas antibodies rapidly induces apoptosis in susceptible cells. To characterize the molecular events involved in Fas-induced apoptosis, we examined the contribution of two subgroups of the mitogen-activated protein (MAP) kinase family, the Jun kinases or stress-activated protein kinases (JNKs/SAPKs) and the extracellular signal-regulated kinases (ERKs), in a Fas-sensitive neuroblastoma cell line. Here we show that both JNK and ERK protein kinases were activated upon Fas crosslinking through a Ras-dependent mechanism. Interference with either the JNK or ERK pathway by ectopic expression of dominant-interfering mutant proteins blocked Fas-mediated apoptosis. ERK activation was transient and associated with induced expression of the Fas receptor. In contrast, JNK activation was sustained and correlated with the onset of apoptosis. These data indicate that the ERK and the JNK groups of MAP kinases cooperate in the induction of cell death by Fas. Inhibition of Fas killing by an interleukin 1β-converting enzyme (ICE)-like protease inhibitor peptide did not modify Fas-induced JNK activation upon Fas ligation. In contrast, changes in Bcl-2 level due to expression of sense and antisense vectors influenced the sensitivity to Fas killing and Fas-induced JNK activation.